Periodismo tradicional vs periodismo iterativo caso: Diario El Universo, año 2020 - Mosquera Valero, Karen Andrea (2020)
The purpose of this research work was to identify the existing differences between traditional journalism vs iterative journalism, in addition to analyzing whether they are present in the informative publications of Diario El Universo, of the year 2020. For this, it was considered convenient to carry out a "case study" that would allow to investigate in depth the way in which this print media uses these types of journalism to communicate through two different contexts, traditional and digital. Understanding that the importance of this issue lies in highlighting how a traditional medium despite its origin, can adapt to technological changes produced by the internet. Fading advantage of them as a transformation initiative, which allows them to embrace new contexts and experience new ways of doing journalism. And it is that from a broad analysis of this important media in the country, it was concluded that both types of journalism are definitely used as positive initiatives that benefit the ways of communicating, however each one in its different channels presents limitations and risks that If they are not taken care of, they can generate problems for the journalist, especially damaging their credibility, since the main divergence between the two lies in the order in which they contrast and publish the informative note. For this, an interview was applied to an editor of the newspaper El Universo, who, according to her experience in it, corroborated what was observed and analyzed in eight news items selected from the two channels managed by this important medium, the Traditional (press) and el Digital (website).